Icariin and Its Metabolites as Potential Protective Phytochemicals Against Alzheimer’s Disease - Angeloni, Cristina; Barbalace, Maria Cristina; Hrelia, Silvana (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD) is a neurodegenerative disorder affecting more than 35 million people worldwide. As the prevalence of AD is dramatically rising, there is an earnest need for the identification of effective therapies. Available drug treatments only target the symptoms and do not halt the progression of this disorder; thus, the use of natural compounds has been proposed as an alternative intervention strategy. Icariin, a prenylated flavonoid, has several therapeutic effects, including osteoporosis prevention, sexual dysfunction amelioration, immune system modulation, and improvement of cardiovascular function. Substantial studies indicate that icariin may be beneficial to AD by reducing the production of extracellular amyloid plaques and intracellular neurofibrillary tangles and inhibiting phosphodiesterase-5 activity. Moreover, increasing evidence has indicated that icariin exerts a protective role in AD also by limiting inflammation, oxidative stress and reducing potential risk factors for AD such as atherosclerosis. This mini-review discusses the multiple potential mechanisms of action of icariin on the pathobiology of AD including explanation regarding its bioavailability, metabolism and pharmacokinetic.